The epg5 knockout zebrafish line: a model to study Vici syndrome. Issue 8 (3rd August 2019) - Meneghetti, Giacomo; Skobo, Tatjana; Chrisam, Martina; Facchinello, Nicola; Fontana, Camilla Maria; Bellesso, Stefania; Sabatelli, Patrizia; Raggi, Flavia; Cecconi, Francesco; Bonaldo, Paolo; Dalla Valle, Luisa
ABSTRACT: The EPG5 protein is a RAB7A effector involved in fusion specificity between autophagosomes and late endosomes or lysosomes during macroautophagy/autophagy. Mutations in the human EPG5 gene cause a rare and severe multisystem disorder called Vici syndrome. In this work, we show that zebrafish epg5 -/- mutants from both heterozygous and incrossed homozygous matings are viable and can develop to the age of sexual maturity without conspicuous defects in external appearance. In agreement with the dysfunctional autophagy of Vici syndrome, western blot revealed higher levels of the Lc3-II autophagy marker in epg5 - /- mutants with respect to wild type controls. Moreover, starvation elicited higher accumulation of Lc3-II in epg5 - /- than in wild type larvae, together with a significant reduction of skeletal muscle birefringence. Accordingly, muscle ultrastructural analysis revealed accumulation of degradation-defective autolysosomes in starved epg5 - /- mutants. By aging, epg5 - /- mutants showed impaired motility and muscle thinning, together with accumulation of non-degradative autophagic vacuoles. Furthermore, epg5 - /- adults displayed morphological alterations in gonads and heart. These findings point at the zebrafish epg5 mutant as a valuable model for EPG5-related disorders, thus providing a new tool for dissecting the contribution of EPG5 on the onset and progression of Vici syndrome as well as for the screening of autophagy-stimulating drugs. Abbreviations: ATG: autophagy related; cDNA: complementary DNA; DIG: digoxigenin; dpf: days post-fertilization; EGFP: enhanced green fluorescent protein; EPG: ectopic P granules; GFP: green fluorescent protein; hpf: hours post-fertilization; IL1B: interleukin 1 beta; Lc3-II: lipidated Lc3; mpf: months post-fertilization; mRNA: messenger RNA; NMD: nonsense-mediated mRNA decay; PCR: polymerase chain reaction; qPCR: real time-polymerase chain reaction; RAB7A/RAB7: RAB7a, member RAS oncogene family; RACE: rapid amplification of cDNA ends; RFP: red fluorescent protein; RT-PCR: reverse transcriptase-polymerase chain reaction; SEM: standard error of the mean; sgRNA: guide RNA; UTR: untranslated region; WMISH: whole mount in situ hybridization; WT: wild type.